A Comparison of Cadastre in Slovakia and Poland - Jurkiewicz Magdalena; Hudecová Ľubica; Kyseľ Peter; Klapa Przemysław; Mika Monika; Ślusarski Marek (Slovak Journal of Civil Engineering, 2023)
Many analogies can be drawn from the cadastre in Poland and Slovakia, because of the partly shared history of the Austro-Hungarian Empire, World Wars I and II, and the influence of the Communist regime. However, its development over the years has taken different forms and rules of operation in both countries. Currently, from a European perspective, there are efforts to standardise cadastral systems to expand their functionality for land administration and to accommodate social needs.